PENINGKATAN KEAKTIFAN BERTANYA MELALUI INKUIRI TERBIMBING SISWA KELAS X MIA 6 SMA NEGERI 1 KARANGANYAR TAHUN PELAJARAN 2015/2016 - Kusumawardani, Wahyu; Maridi, Maridi; Muzzayyinah, Muzzayyinah (Universitas Sebelas Maret, 2016)
The research aims to apply the guided inquiry model to improve questioning activity in the learning material â€œAnimaliaâ€ in class X Science 6 of SMA Negeri 1 Karanganyar in 2015/2016 academic year. The research was a classroom action research which was done in three cycles covering planning, action, observation, and reflection stage. The learning model applied was guided inquiry model including six stages, they are: observe, formulate inquiry question, develop hypothesis, design and conduct investigation, analyze data, and arguing. Subject of the research was 40 students of X Science 6 of SMA Negeri 1 Karanganyar in 2015/2016 academic year. The data of the research was gained by doing observation, interview, and documentation. The writer analyzed the data using descriptive qualitative analyzing technique. The result shows that applying guided inquiry model improve the score of questioning activity in the learning material â€œAnimaliaâ€ of X Science 6 students of SMA Negeri 1 Karanganyar in 2015/2016 academic year. The improvement of studentsâ€™ questioning activity is showed from the improving score of studentsâ€™ questioning activity score to teacher, to students, and in wrtitten from pre cycle stage until cycle 3. The score of questioning activity from students to teacher improves from 7,5% or 3 students in pre cycle to 40% or 16 students in cycle 1, 50% or 20 students in cycle 2 and 55% or 22 student in cycle 3. The score of questioning activity from students to student improves from 0% or 0 students in pre cycle to 80% or 32 students in cycle 1, 95% or 38 students in cycle 2 and cycle 3.The score of questioning activity from students in written improves from 0% or 0 students in pre cycle to 37,5% or 15 students in cycle 1, 45% or 18 students in cycle 2 and 52,5% or 21 student in cycle 3. Data improvement of each aspect of studentsâ€™ questioning activity from pre cycle until cycle 3 has reached the research target (â‰¥50%). Based on the result, it can be concluded that guided inquiry model improves questioning activity in learning material â€œAnimaliaâ€ of class X Science 6 of SMA Negeri 1 Karanganyar in 2015/2016 academic year.Â Keywords: questioning activity, guided inquiry